The pre-B-cell receptor induces silencing of VpreB and λ5 transcription - Parker, Mathew J (Nature Publishing Group, 2005)
The pre-B-cell receptor (pre-BCR), composed of Ig heavy and surrogate light chain (SLC), signals pre-BII-cell proliferative expansion. We have investigated whether the pre-BCR also signals downregulation of the SLC genes (VpreB and λ5), thereby limiting this expansion. We demonstrate that, as BM cells progress from the pre-BI to large pre-BII-cell stage, there is a shift from bi- to mono-allelic λ5 transcription, while the second allele is silenced in small pre-BII cells. A VpreB1-promoter-driven transgene shows the same pattern, therefore suggesting that VpreB1 is similarly regulated and thereby defines the promoter as a target for transcriptional silencing. Analyses of pre-BCR-deficient mice show a temporal delay in λ5 downregulation, thereby demonstrating that the pre-BCR is essential for monoallelic silencing at the large pre-BII-cell stage. Our data also suggest that SLP-65 is one of the signaling components important for this process. Furthermore, the VpreB1/λ5 alleles undergo dynamic changes with respect to nuclear positioning and heterochromatin association, thereby providing a possible mechanism for their transcriptional silencing.